Anterior Segment Optical Coherence Tomography Angiography and Optical Coherence Tomography in the Evaluation of Episcleritis and Scleritis. (17th February 2021) - Hau, Scott C.; Devarajan, Kavya; Ang, Marcus
ABSTRACT: Purpose : To evaluate the feasibility of using anterior segment optical coherence tomography (AS-OCT) and AS-OCT angiography (AS-OCTA) in assessing patients with episcleritis and scleritis. Methods : Degree of vascularity [vessel density index (VDI)], measured with AS-OCTA, and sclera thickness [conjunctiva epithelium (CE), conjunctiva/episclera complex (CEC), and episclera/sclera complex (ESC)], measured with AS-OCT were compared. Results : A total of 37 eyes (13 episcleritis, 11 scleritis, 13 controls) were analyzed. VDI was lowest for controls for the various tissue depths ( p < .001). Episcleritis versus scleritis revealed a significant difference in VDI at ESC (38.1 ± 11.4% vs 46.4 ± 6.4%; p = .03). Mean sclera thickness was lower in controls for CE ( p < .001), CEC ( p < .001) but not for ESC ( p = .54). Conclusions : The degree of vascularity and tissue thickness were different between episcleritis, scleritis and controls. AS-OCTA and AS-OCT may potentially be useful in evaluating patients with scleral inflammation.